2016
DOI: 10.1111/tbj.12731
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Angiosarcoma: A Retrospective Study of 36 Cases from a Single Chinese Medical Institute with Clinicopathologic and Radiologic Correlations

Abstract: The aim of this study was to present our experience with primary breast angiosarcoma (PBA) by describing a large series of cases with an emphasis on clinicopathologic and radiologic correlations. Thirty-six cases of PBA diagnosed at our institution between 2006 and 2014 were retrospectively evaluated. All but one case occurred in women with a median age of 35.5 years. The majority of patients presented with a deeply located painless mass, whereas a minority manifested as diffuse enlargement or swelling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Wang et al conducted the only retrospective study that indicated angiosarcoma with pulmonary metastasis often presents with multiple pulmonary nodules and DAH. The common initial misdiagnoses included tuberculosis, auto‐immune‐related vasculitis, non‐tuberculous infectious disease, and constrictive pericarditis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al conducted the only retrospective study that indicated angiosarcoma with pulmonary metastasis often presents with multiple pulmonary nodules and DAH. The common initial misdiagnoses included tuberculosis, auto‐immune‐related vasculitis, non‐tuberculous infectious disease, and constrictive pericarditis .…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse alveolar haemorrhage (DAH) is a distinct clinicopathological syndrome characterized by the accumulation of intra‐alveolar red blood cells originating from the alveolar capillaries . DAH is associated with pulmonary capillaritis, bland pulmonary haemorrhage, diffuse alveolar damage, and miscellaneous histology . However, neoplastic diseases are not commonly considered in the differential diagnosis of DAH.…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis is variable according to this grade. It includes benign haemangioma, angiomyolipoma, melanoma, undifferentiated carcinoma, stromal sarcoma and reactive spindle cell proliferative lesion [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The age range of our study group differs from that of patients enrolled in the Wang et al study. In this study, the median age was 35.5 (17 to 68 years) 8 . Johnson et al and Nascimento et al indicate higher prevalence of pas in the right mamma 2,9 .…”
Section: Discussionmentioning
confidence: 99%